Percutaneous Vertebroplasty: A Special Syringe for Cement Injection - Al-Assir, Imad; Perez-Higueras, Antonio; Florensa, Jose; Muñoz, Alberto; Cuesta, Emilio (American Journal of Neuroradiology, 2000)
Summary: Percutaneous vertebroplasty is an effective treatment for many focal vertebral lesions. Methyl methacrylate is too viscous to be handled without difficulty in the conventional way because injection time is short. The operator is left with little time and must fumble with multiple syringes. We describe a special screw-system syringe that decreases the effort needed to inject the cement. In addition, it can standardize the injection pressures and control the injected volume because the threaded plunger affords greater control of injection pressure and volume delivered than does the conventional method.